S09.1 Molecular Detection of Antimicrobial Resistance in STI Pathogens. (13th July 2013) - Whiley, D; Chen, M; Donovan, B; Fairley, C; Guy, R; Kaldor, J; Regan, D; Trembizki, E; Ward, J; Lahra, M
Abstract : The emergence of antimicrobial resistance (AMR) among sexually transmitted infections (STI) is a cause for global concern, and is epitomised by the fact we are now running out of treatment options for gonorrhoea. The role of AMR surveillance is now more important than ever. Ideally, AMR surveillance should be fast, easy, inexpensive, accessible, reproducible across testing methods, and provide clinically meaningful information to inform treatment strategies. In reality this is not the case, with AMR surveillance activities for STIs typically weak or non-existent in many parts of the world. Molecular methods have the potential to enhance AMR surveillance, particularly for organisms that cannot easily or readily be characterised phenotypically; which is the case for most STIs. The challenges for molecular surveillance are however many and include factors such as; the mechanisms of resistance may be many or otherwise unknown, they may miss novel mutations, the technology can be expensive, they need specialised laboratories and trained staff, and that their specificity can be undermined where target sequences are shared across different species. Despite these challenges, such methods are being developed and are now finding their way into routine settings. Advances in molecular technology and expanding knowledge of resistance mechanisms continue to pave new directions in this important area.